ANALYSIS OF BPKH FUND PLACEMENT AND INTERNAL FACTORS IMPACT ON ISLAMIC BANK PROFITABILITY (2010–2023) - Ahmad, Hisyam Abiyya; Fadli, Faishal (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study examines the impact of BPKH (Hajj Fund Management Agency) placements on the profitability of Islamic Commercial Banks in the period of 2010–2023. Profitability is measured using the Return on Assets (ROA) variable, while the independent variables consist of BPKH fund placement (dummy), along with other financial ratios such as Third Party Funds (DPK), Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR). Control variables include macroeconomic factors: inflation and the Bank Indonesia interest rate. This research employs a quantitative approach using panel data and finds that the Fixed Effect Model (FEM) is the most appropriate, based on the results of Chow and Hausman tests. The findings show that BPKH fund placements do not have a significant impact on ROA. Similarly, NPF, CAR, inflation, and interest rate variables also show no significant influence. Meanwhile, the variables FDR, DPK, and BOPO have a significant negative impact on ROA. Conversely, total assets have a significant positive effect on ROA. This study concludes that operational efficiency and effective fund management are crucial in enhancing profitability, and that optimization of fund placements—including Hajj funds—is necessary